Features of the Creation And Functioning Of Free Economic Zones In Uzbekistan - et. al., Kuzieva Nargiza Ramazanovna, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The article examines such tasks as the role of free economic zones in the economy of the state, the features of the emergence and development of tax regimes, free economic zones as a category in the economy and their need for the development of the country. The article provides an analysis of domestic, their development of free economic zones and the existing tax regime, an analysis of the regulatory framework for the creation and functioning of free economic zones, as well as an analysis of the economic indicators of free economic zones and the tax incentives they use.